Bridging Qualitative and Quantitative Methods in Organizational Research: Applications of Synthetic Control Methodology in the U.S. Automobile Industry - Fremeth, Adam R.; Holburn, Guy L. F.; Richter, Brian K. (Organization Science, 2016)
We assess the utility of synthetic control, a recently developed empirical methodology, for applications in organizational research. Synthetic control acts as a bridge between qualitative and quantitative research methods by enabling researchers to estimate treatment effects in contexts with small samples or few occurrences of a phenomenon or treatment event. The method constructs a counterfactual of a focal firm, or other observational unit, based on an objectively weighted combination of a small number of comparable but untreated firms. By comparing the firm’s actual performance to its counterfactual replica without treatment, synthetic control estimates, under certain assumptions, the magnitude and direction of treatment effects. We illustrate and critique the method in the context of the U.S. auto industry by estimating (a) the effect of government intervention in Chrysler’s management from 2009 to 2011 on its sales volumes and (b) the impact of Toyota’s 2010 “acceleration crisis” on Camry sales.